Implementation of the Mobile Waste Bank Program (BAGIAK) (Study on the Governance of the BAGIAK Program at the Main Waste Bank Office in Banyuwangi Regency) - Sari, Widia Novita; Wilujeng, Sri; Agustina, Erna (PT. LITERASI SAINS NUSANTARA, 2024)
The active mobile waste bank (BAGIAK) is an effort to collect the proceeds from sorting inorganic waste from the community in the form of waste savings that can be taken in the form of money. The lack of employees in the field of waste transportation and the lack of adequate facilities and infrastructure at Banyuwangi's main waste bank are important concerns in efforts to manage sustainable waste. Objective: To find out and describe the achievements of the Implementation of the Giat Keliling (BAGIAK) Waste Bank Program (Study on the Management of the BAGIAK Program at the Banyuwangi Regency Main Waste Bank Office. The research method is qualitative and is a type of descriptive research. This implementation is focused on the ideas of George C. Edward III in Winarno 1) Communication, 2) Resources, 3) Disposition, and 4) Bureaucratic Structure. Research results: First, communication about the socialization of the program has not reached all levels of society. This shows that education about the benefits of the program still needs to be improved. Second, resources, number of fleets and number of employees available are still limited. This causes the actively traveling waste bank officers to have to work harder and spend more time. Third, Disposition, employees have shown good performance in carrying out their duties and have commitment and dedication to carry out them. Each level and section in the organizational structure has clear duties and responsibilities, so that there is no overlapping of work and is well organized. This is because the structure is in accordance with Standard Operating Procedures (SOP).